Factores psicologicos asociados al embarazo precoz de una estudiante de primero de bachillerato de la Unidad Educativa Quevedo - Ube Cabrera, Narcisa Lisbeth (2021)
The present investigative work includes a fairly common problem in today's society, which includes examining the psychological factors associated with the early pregnancy of a first year high school student from the “Quevedo” educational unit. One of the most important challenges is to preserve the Young pregnant women studying or finishing their studies, considering the situation of the student in the educational unit, the parents, teachers and the authorities of the organization, have applied tactics so as not to affect their emotional state or educational performance. A clinical case of a 15-year-old pregnant girl is presented, who was diagnosed with a persistent depressive disorder, in the educational unit it was possible to recognize the most predominant signs of this disorder, through the interview and application of different techniques psychological.